A community living management program for people with disabilities who have moved out of nursing homes: a pilot study. Issue 8 (9th April 2016) - Lee, Danbi; Hammel, Joy; Wilson, Tom
Abstract: Purpose : This study describes implementation and evaluation of the Stepping Stones program, a community living management program designed to assist people with disabilities to gain community living skills after moving out of nursing homes. Methods : Thirteen people with diverse disabilities participated in the 10-week Stepping Stones program. The participants attended two sessions a day every week, over a 5-week period. Interviewer-administered surveys were used at baseline and 1 week post-intervention to evaluate the impact of the program. Focus group interviews were conducted at 1 week post-intervention. Results : Analyses of quantitative data demonstrated improved self-efficacy in community living management skills, with medium-to-high effect sizes. Participants reported improved sense of empowerment and confidence in finding resources and managing community living. They also reported high satisfaction with the program. Conclusions : Preliminary findings suggest that the Stepping Stones program is beneficial to the target group. The study indicates that application of social learning and self-efficacy theories is effective to empower and enable people with disabilities to manage their lives in the community. The Stepping Stones program may be provided as a risk management intervention after individuals' transition into the community. Implications for Rehabilitation: Long-term institutionalization negatively influences people with disabilities' self-esteem, autonomy and ability to independently live in the community. Successful community living requires complex management involving the coordination of personal, social, resource and environmental factors. This study shows that programming on choice and control and community living skill development improved participants' confidence in managing community living.